PENGEMBANGAN E-MODUL BARISAN DAN DERET BERBANTUAN LECTORA UNTUK MENGEKSPLOR KEMAMPUAN KONEKSI MATEMATIS SISWA SMK - Lisbadiyah, Ulpah; Ratnaningsih, Nani; Lestari, Puji (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2023)
The research produced an e-module of Lectora-assisted sequences and series to explore the mathematical connection abilities of Vocational High School students as well as to analyze and describe the quality of effectiveness of the mathematical connection abilities of Vocational High School students after using the Lectora-assisted sequence and series e-module. The method used in this study is the research and development method (Research & Development) with the ADDIE development model through the Analyze, Design, Develop, Implement and Evaluate stages to obtain a product that is valid and feasible to use. Based on the results of research and development, the researcher analyzes the stage conduct material and media needs analysis. At the design stage the researcher makes flowcharts and storyboards, designs test instruments, compiles validation sheets for material experts and media experts, creates user response questionnaires, the develop stage produces products that have been designed, conducts expert tests on material experts and media experts with validation results at category